Abundant Molecular Gas in the Central Region of Lenticular Galaxy PGC 39535 - Jiantong Cui; Qiusheng Gu; Shiying Lu; Zhengyi Chen; Can Xu; Zeyu Gao (The Astrophysical Journal)
Lenticular galaxies (S0s) in the local Universe are generally absent of recent star formation and lack molecular gas. In this paper, we investigate one massive ( M _* ∼ 5 × 10 ^10 M _⊙ ) star-forming S0, PGC 39535, with the Northern Extended Millimeter Array (NOEMA). Using optical data from the Sloan Digital Sky Survey IV Mapping Nearby Galaxies at the Apache Point Observatory survey, we find star formation mainly concentrates in the central region of PGC 39535. The total star formation rate estimated using extinction-corrected H α flux is 1.57 M _⊙ yr ^−1 . The results of the NOEMA observation suggest that the molecular gas mainly concentrates in the central regions as a gaseous bar and a ring-like structure, and shows similar kinematics as the stellar and ionized gas components. The total molecular gas mass estimated from CO(1–0) is (5.42 ± 1.52) × 10 ^9 M _⊙ . We find PGC 39535 lies on the star-forming main sequence but falls below the Kennicutt–Schmidt relation of spiral galaxies, suggesting that the star formation efficiency may be suppressed by the massive bulge. The existence of a second Gaussian component in the CO spectrum of the central region indicates possible gas flows. Furthermore, our analyses suggest that PGC 39535 resides in the center of a massive group and the derived star formation history indicates it may experience a series of gas-rich mergers over the past 2–7 Gyr.